The Vision of 5G and Cell-Free Communication Networks in Malaysia - Mahdi M.N.; Mohamed K.S.; Ahmad A.R.; Subhi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
4G mobile communication systems; Computational complexity; Cost effectiveness; Deep learning; Queueing networks; Artificial intelligence technologies; Bandwidth capacity; Cellular network; Computer training; Data explosion; Guaranteed access; Industrial sensor; Location optimization; 5G mobile communication systems